Feasibility analysis of incorporating infertility into medical insurance in China - Wang, Lin; Zhu, Ye; Wang, Tong; Xu, Xinrong; Tang, Qiuqin; Li, Jinhui; Wang, Yanchen; Hu, Weiyue; Wu, Wei (Frontiers in Endocrinology, 2022)
In recent years, the incidence of infertility has been increasing gradually, while the natural rate of population growth is declining or even zero growth. China is observed to enter a depth of aging society, leading to more severe infertility. Infertility patients face many predicaments, and many unreasonable behaviors existed in seeking medical diagnosis and treatment, of which the main influencing factor is economic condition. In China, Beijing has taken the lead in providing medical insurance for 16 assisted reproductive technology items. Assuming that all infertile couples with the option of assisted reproduction are treated, there would be a huge market gap. The reimbursement rate can be adjusted based on some factors within the affordable range of the medical insurance fund. Progress on infertility coverage in other countries was also reviewed. This paper cited the data of medical insurance funds in China in recent four years as a reference. Based on the data, it is not currently able to cover all the costs of infertility diagnosis and treatment during the research period. But it is feasible to access selective reimbursement and subsidies for those in particular need, as well as to develop some commercial insurances. There is a big gap in the application of assisted reproductive technology between China and developed countries. More comprehensive and constructive policies should be formulated countrywide to standardize the market. Also, assisted reproduction-related technologies and acceleration of the domestic medical apparatus and instruments replacement should be improved to reduce the cost.